Persepsi Remaja Laki-laki Terhadap Hubungan Seksual Pranikah: Studi Kualitatif Sekolah Menengah Kejuruan - Iqoh Qothrunnada; Hardin La Ramba; Shinta Prawitasari (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2026)
Adolescence is a transitional phase that is vulnerable to various risky behaviors, including premarital sexual relations. This behavior becomes a global public health issue because it can cause negative impacts such as unwanted pregnancies, sexually transmitted infections, and psycholoical disorders. The prevalence of sexual relationships before marriage in indonesia is increasing. This study aims to explore male adolescents’s perceptions of premarital sexual relations andthe factis that influence the, in order ro provide insights for reproductive health education and prevention efforts. This study uses a descriptive qualitative approach with purposive sampling techniques involving 10 male students in grade XI. Data were obtained through semi-structured in-depth interviews and analyzed using Braun and Clarke’s analysis. The research result produced fourmain themes, namely adolescents perceptions of premarital sexual relationships, driving factors, the impact of premarital sexual relatioships, and adolescents attitude towards premarital sexual relatinships. Adolescents males perceptions of premarital sexual relationships are influenced by internal and external factors, with the majority aware of the negative risks. This study recommends strengthening comprehensive sexual education involving families, schools,and communities to shape healthy and reponsible behavior.